Domestic violence against women: representations of health professionals - Vera Lúcia de Oliveira Gomes; Camila Daiane Silva; Denize Cristina de Oliveira; Daniele Ferreira Acosta; Cristiane Lopes Amarijo (Universidade de São Paulo, 2015)
AbstractObjective: to analyze the representations about domestic violence against women, among health professionals of Family Health Units.Method: qualitative study based on the Theory of Social Representations. Data were collected by means of evocations and interviews, treating them in the Ensemble de Programmes Pemettant L'Analyse des Evocations software - EVOC and content analysis.Results: nurses, physicians, nursing technicians and community health agents participated. The evocations were answered by 201 professionals and, of these, 64 were interviewed. The central core of this representation, comprised by the terms "aggression", "physical-aggression", "cowardice" and "lack of respect", which have negative connotations and were cited by interviewees. In the contrast zone, comprised by the terms "abuse", "abuse-power", "pain", "humiliation", "impunity", "suffering", "sadness" and "violence", two subgroups were identified. The first periphery contains the terms "fear", evoked most often, followed by "revolt", "low self-esteem" and "submission", and in the second periphery "acceptance" and "professional support".Conclusion: this is a structured representation since it contains conceptual, imagetic and attitudinal elements. The subgroups were comprised by professionals working in the rural area and by those who had completed their professional training course in or after 2004. These presented a representation of violence different from the representation of the general group, although all demonstrated a negative connotation of this phenomenon.